Geography And Social Movement : Comparing Antinuclear Activism in the Boston Area - Miller, Byron A., 1957-; Project Muse. (Minneapolis : University of Minnesota Press, 2000)
Byron A. Miller directly addresses the implications of space, place, and scale in social movement mobilization, and then demonstrates their significance in a detailed comparative analysis of peace movements in three municipalities around Boston.
Acknowledgments; Introduction; 1. Missing Geography: Social Movements on the Head of a Pin?; 2. A Geographic Model of Social Movement Mobilization; 3. Place Matters: Interests, Resources, and Opportunities; 4. Space, Place, and Mobilization; 5. Geographic Scale, Mobilization, and the Representation of Defense Investment; 6. Local and Central State Political Opportunity Structures: Material Interests and the Shifting Scale of Struggle; Conclusion: The Difference Geography Makes; Notes; References; Index.
Includes bibliographical references (p. 177-205) and index.
Description based on print version record.
JSTOR
Keywords: Social change; Social movements -- Massachusetts -- Boston; Social movements; Antinuclear movement -- Massachusetts -- Boston; Mouvements sociaux -- Massachusetts -- Boston; Mouvements sociaux; Mouvement antinucléaire -- Massachusetts -- Boston; social movements; SOCIAL SCIENCE -- Human Geography; Antinuclear movement; Social change; Social movements; Massachusetts -- Boston